Characteristics of Modified Leghemoglobins Isolated from Soybean (Glycine max Merr.) Root Nodules. - Jun, H. K. (1994)
Hemoprotein derivatives of an abundant soybean (Glycine max Merr.) root nodule leghemoglobin, Lba, were studied for their modified spectral characteristics and physical properties. Three modified hemoprotein derivatives of Lba (Lbam1, Lbam2, and Lbam3) were purified by preparative isoelectric focusing. The ferric forms of these pigments were green and exhibited anomalous spectra in the visible region as compared to the Lba3+ forms. These modified pigments showed a hypochromic shift of 10 nm for the charge transfer absorption maximum; however, differences were not apparent in the Soret region. Upon binding with nicotinate, the [alpha] and [beta] bands were shifted significantly into the red region as compared to the Lba3+ nicotinate complex. The three Lbam fractions were reduced by dithionite or by NADH in the presence of riboflavin. Lbam2+ also bound nicotinate and displayed absorption spectra indistinguishable from those of Lba2+ nicotinate. In contrast to Lba2+, Lbam2+ displayed aberrant spectra when bound with either O2 or CO. These complexes exhibited a prominent charge transfer band at approximately 620 nm and failed to exhibit spectra characteristic of Lba2+O2 and Lba2+CO. The protein moiety of these modified pigments was intact because their tyrosine/tryptophan ratios and their amino acid compositions were identical with those of Lba, nor were differences observed in the peptide profiles resulting from trypsin digests of purified Lba and Lbams. Automated Edman degradation of selected peaks further confirmed the intactness of the protein backbone including the absence of deamination. Pyridine hemochromogen for heme from Lbams could be formed, and the spectra displayed distinct differences compared to those of Lba. A new peak at 580 nm and a loss of a peak at 480 nm were observed for all three Lbams.